Modern trends in the formulation of microparticles for lung delivery using porogens: methods, principles and examples - Peštálová, Andrea; Gajdziok, Jan (Pharmaceutical development and technology, 2024)
Inhalation drug administration is increasingly used for local pharmacotherapy of lung disorders and as an alternative route for systemic drug delivery. Modern inhalation powder systems aim to target drug deposition in the required site of action. Large porous particles (LPP), characterized by an aerodynamic diameter over 5 μm, density below 0.4 g/cm3, and the ability to avoid protective lung mechanisms, come to the forefront of the research. They are mostly prepared by spray techniques such as spray drying or lyophilization using pore-forming substances (porogens). These substances could be gaseous, solid, or liquid, and their selection depends on their polarity, solubility, and mutual compatibility with the carrier material and the drug. According to the pores-forming mechanism, porogens can be divided into groups, such as osmogens, extractable porogens, and porogens developing gases during decomposition. This review characterizes modern trends in the formulation of solid microparticles for lung delivery; describes the mechanisms of action of the most often used porogens, discusses their applicability in various formulation methods, emphasizes spray techniques; and documents discussed topics by examples from experimental studies.
Keywords: poréznost; farmaceutická chemie; Porosity; Particle Size; plíce; prášky, zásypy, pudry; Powders; Microparticles; porogens; aplikace inhalační; Chemistry, Pharmaceutical; spray drying; Lung; Drug Delivery Systems; Animals; lidé; Drug Compounding; Humans; zvířata; porosity; velikost částic; porous particles; příprava léků; Administration, Inhalation; inhalation; lékové transportní systémy